2022
DOI: 10.3390/molecules27154866
|View full text |Cite
|
Sign up to set email alerts
|

Light and Potassium Improve the Quality of Dendrobium officinale through Optimizing Transcriptomic and Metabolomic Alteration

Abstract: Background: Dendrobium officinale is a perennial epiphytic herb in Orchidaceae. Cultivated products are the main alternative for clinical application due to the shortage of wild resources. However, the phenotype and quality of D. officinale have changed post-artificial cultivation, and environmental cues such as light, temperature, water, and nutrition supply are the major influencing factors. This study aims to unveil the mechanisms beneath the cultivation-induced variation by analyzing the changes of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Previous research has reported on the increase in flavonoid content and associated gene expression by UV-B and MeJA treatments [ 23 , 24 , 25 ]. These compounds are produced as antioxidants for the removal of free radicals caused by abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported on the increase in flavonoid content and associated gene expression by UV-B and MeJA treatments [ 23 , 24 , 25 ]. These compounds are produced as antioxidants for the removal of free radicals caused by abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the production of polysaccharides D. officinale decreases gradually, with the increase in altitude and decrease in temperature ( He et al., 2022 ). Light-treatment affected the accumulation of primary and secondary metabolites in D. officinale , especially the biosynthesis of flavonoids, which the components of flavonoid glycosides were significantly upregulated ( Jia et al., 2022 ). Zuo et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the production of polysaccharides D. officinale decreases gradually, with the increase in altitude and decrease in temperature (He et al, 2022). Light-treatment affected the accumulation of primary and secondary metabolites in D. officinale, especially the biosynthesis of flavonoids, which the components of flavonoid glycosides were significantly upregulated (Jia et al, 2022). Zuo et al, (2020) conducted a comparative analysis of the metabolomics of D. officinale under different cultivation substrates, and they found that only three shared metabolites differed significantly among the different comparisons.…”
Section: A B Cmentioning
confidence: 99%